Breaking the unvirtuous cycle: barriers and opportunities for research and development in Paraguay. A case study - Donna, María Lucila Gonzalez; León, María Luisa Cabañas; Colas, Cinthia Gauna; Gunsett, Alicia Pomata; Maniero, Silvia Ferreira; Osuna, David Olivares; Klimovsky, Ezequiel; Coradini, Lucas; Enrico, Diego; Chacón, Matías; Waisberg, Federico (Frontiers in Medicine, 2023)
Introduction Medical research and development (R&D) is an undoubtedly relevant activity to drive innovation, improve healthcare policies and bring patients treatment opportunities for common and rare diseases. Equity and inclusion are matters of concern in research. High-income countries’ research teams are more likely to have more impactful publications, grant funding, and clinical trials than middle or low-income countries. Low budget allocations to R&D and existing gaps in regulatory frameworks are some obstacles to growth. This unvirtuous cycle results in scarce advances in common endemic diseases and the underrepresentation of specific populations in innovative therapeutics research. Materials and methods We conducted a policy review and qualitative research to determine the principal characteristics of basic and clinical medical research in Paraguay, as well as barriers and facilitators to improve innovative R&D strategies in this country. To this aim, we examined published articles from 2005 to 2020, the organizational structure of national research agencies, the current regulation framework, and the composition and experience of local research groups and ethical review boards (ERBs). In addition, we performed semi-structured interviews to evaluate perceptions and expectations from different stakeholders, including investigators, ERBs members, sponsor associates, and Regulatory Agency executive staff. Results In 2018, Paraguay ranked 10th out of 12 South American countries in total number of publications and cumulative h-index score. Total Gross Domestic Product (GDP) allocation for R&D was 0.15%, ranking eighth out of 12 in the region. In 2021, the number of trials registered on ClinicalTrials.gov was 52, with only 16 ongoing recruiting studies at that time. Some of the main barriers identified included low incentives for academic careers and lack of experience in pharmaceutical research. An emergent necessity to develop a straight- forward normative framework was detected. Main facilitators included the development of two research initiative programs (PRONII and PROCIENCIA) from CONACYT (National Council of Science and Technology) which were associated with higher budget allocation and total number of publications in the 2011 to 2017 period. A total of six stakeholders participated in the semi-structured surveys. Interviewees highlighted the necessity of a centralized policy to promote R&D, which incorporates investigators and ERBs training, the development of standardized procedures, and the dissemination of research activities. Sponsor associates underlined that real-world evidence may represent a distinctive opportunity to enhance local research. Conclusion Coordinated efforts are needed to break the unvirtuous cycle. There is an increasing interest in enhancing health research in Paraguay, materialized in the creation of specific programs that encourage the collaborative work of healthcare providers, basic scientists, and private investors. Nonetheless, a comprehensive approach is needed also to strengthen regulatory agencies and attract external sponsorship. While modern and currently popular topics, including artificial intelligence, real-world data, and translational research may represent key opportunities to seek investment, special policies should be adopted to prioritize research on the determinants of health in the Paraguayan population.